Penyuluhan Kelompok Pedagang Kaki Lima melalui Kebersihan Lingkungan sebagai Upaya Peningkatan Ekonomi dan Kesehatan Masyarakat - Iin Nurbudiyani; Endang Sri Suyati; Arna Purtina (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
When you hear the term Street Vendors (PKL), it comes to mind that conditions are slum, dirty, irregular, black, dirty, unhealthy, without tariffs on the price of food or drink menus. Then its existence disturbed the view, seized the sidewalks of the road so that it became the target and object of the order officers because it was selling on the side of the road which was not an area for sale. The police pursued to be disciplined, disappeared briefly appeared again, cat and mouse with trantib officers. Especially in the middle of the city, the protocol road, which is often for officials to pass guests or state guests. Street vendors on one side disturb the eyes, with carts that are worn, dirty, but their existence is needed by the community. They are often referred to as informal sector actors who remain vulnerable to the fluctuation of the dollar. The proof at the time of the company's financial crisis went bankrupt, but street vendors still exist to sell. Even employees who are laid off and laid off become street vendors. In Palangkaraya Street Vendors are almost biased to be found on every street corner, Perda No. 13 of 2009 which regulates the Arrangement, Ordering, and Supervision of Street Vendors seems to have not run optimally. Through this community service, we would like to participate in providing counseling on how beneficial it is to maintain and regulate the street vendors' environment as an effort to improve the economy and public health.